Busy Book for Fun Hijaiyah Letter Learning: Buku Aktivitas Seru untuk Belajar Huruf Hijaiyah - Ummah , Rodiyatul; Nisak, Nur Maslikhatun (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Early childhood learning requires creative strategies to introduce fundamental religious knowledge, including the recognition of Hijaiyah letters as the foundation for reading the Qur’an. Specific background: Conventional methods often emphasize rote memorization, which may reduce children’s engagement and motivation. Knowledge gap: There is limited exploration of interactive and game-based media that integrate fun learning with Islamic education to foster both cognitive and affective development. Aims: This study examines the use of a Busy Book as an interactive learning medium to support children’s ability in recognizing and understanding Hijaiyah letters through playful activities. Results: The Busy Book, designed with 25 colorful pages, provides activities such as coloring, matching, and puzzles, which successfully stimulate children’s interest and improve their ability to identify Hijaiyah letters. Novelty: Unlike traditional learning tools, the Busy Book integrates educational content with interactive play, making the process enjoyable while strengthening retention. Implications: This medium can be an alternative for teachers and parents to introduce Hijaiyah letters in early childhood education, bridging creativity, play, and Islamic values in a single tool. Highlights: Busy Book integrates play and Islamic education. Improves recognition of Hijaiyah letters through creative tasks. Supports engaging and meaningful early childhood learning. Keywords: Busy Book, Hijaiyah Letters, Fun Learning, Early Childhood, Islamic Education